Investigation of chloromethane complexes of cryptophane‐A analogue with butoxy groups using 13C NMR in the solid state and solution along with single crystal X‐ray diffraction. (12th June 2015) - Steiner, Emilie; Mathew, Renny; Zimmermann, Iwan; Brotin, Thierry; Edén, Mattias; Kowalewski, Jozef
Abstract : Host‐guest complexes between cryptophane‐A analogue with butoxy groups (cryptophane‐But) and chloromethanes (chloroform, dichloromethane) were investigated in the solid state by means of magic‐angle spinning 13 C NMR spectroscopy. The separated local fields method with 13 C‐ 1 H dipolar recoupling was used to determine the residual dipolar coupling for the guest molecules encaged in the host cavity. In the case of chloroform guest, the residual dipolar interaction was estimated to be about 19 kHz, consistent with a strongly restricted mobility of the guest in the cavity, while no residual interaction was observed for encaged dichloromethane. In order to rationalize this unexpected result, we performed single crystal X‐ray diffraction studies, which confirmed that both guest molecules indeed were present inside the cryptophane cavity, with a certain level of disorder. To improve the insight in the dynamics, we performed a 13 C NMR spin‐lattice relaxation study for the dichloromethane guest in solution. The system was characterized by chemical exchange, which was slow on the chemical shift time scale but fast with respect to the relaxation rates. Despite these disadvantageous conditions, we demonstrated that the data could be analyzed and that the results were consistent with an isotropic reorientation of dichloromethane within the cryptophane cavity. Copyright © 2015 The Authors. Magnetic Resonance in Chemistry published by John Wiley & Sons Ltd. Abstract : Residual 13 C‐ 1 H dipolar couplings were obtained for chloromethanes (CHCl3 and CH2 Cl2 ) complexed by cryptophane‐But by solid‐state NMR experiments. Information was also obtained from single crystal X‐ray diffraction studies and 13 C NMR experiments in solution.